Motion by stopping: Rectifying Brownian motion of nonspherical particles - Sporer, Susan; Goll, Christian; Mecke, Klaus (Physical Review E, 2008)
We show that Brownian motion is spatially not symmetric for mesoscopic particles embedded in a fluid if the particle is not in thermal equilibrium and its shape is not spherical. In view of applications to molecular motors in biological cells, we sustain nonequilibrium by stopping a nonspherical particle at periodic sites along a filament. Molecular dynamics simulations in a Lennard-Jones fluid demonstrate that directed motion is possible without a ratchet potential or temperature gradients if the asymmetric nonequilibrium relaxation process is hindered by external stopping. Analytical calculations in the ideal gas limit show that motion even against a fluid drift is possible and that the direction of motion can be controlled by the shape of the particle, which is completely characterized by tensorial Minkowski functionals.